Testicular Torsion in Adolescents: A Case Report and Surgical Management Approach - Berry Erida Hasbu; Reeny Purnamasari; Sigit Dwi Pramono; Nadila Nanda Azzahra Ruray (Fakultas Kedokteran Universitas Muslim Indonesia, 2025)
Background: Testicular torsion is a surgical emergency caused by twisting of the spermatic cord, which impedes blood flow to the testicle. If not treated within 4–6 hours of symptom onset, this condition can lead to ischemia, necrosis, and permanent testicular damage. Prompt treatment is crucial to prevent complications. Case Description: A 19-year-old man presented to the emergency department (ED) with severe pain and swelling in the left scrotum for three days. His pain score (VAS) was 5/10. No systemic symptoms were found. Physical examination revealed edema and tenderness in the left scrotum. Scrotal ultrasound revealed an enlarged, heterogeneous, and avascular left testicle, while the right testicle was normal, and left testicular torsion was diagnosed. The patient subsequently underwent orchidectomy for the necrotic left testicle and orchidopexy for the right testicle. Conclusion: Early diagnosis of testicular torsion is crucial to prevent further damage. Doppler ultrasonography was helpful in confirming the diagnosis. The definitive treatment for testicular necrosis is orchidopexy, and orchidopexy is an appropriate approach to prevent recurrence and preserve the function of the remaining testicle